Clinical Profile and Outcome of Children with Sepsis in a Tertiary Care Centre in Eastern Nepal: a Prospective Observational Study. - Bhatta, Mukesh; Kafle, Shyam Prasad; Rai, Basant; Subedi, Rejeena (Birat Journal of Health Sciences, 2021)
Introduction:  Sepsis is a major cause of mortality in children. Understanding the clinical profile of sepsis helps in early diagnosis, treatment and prognostication of the patients.Objectives: This study was done with an objective to assess the clinical features, disease course, etiology and outcome of children diagnosed with sepsis.Methodology:  A prospective observational study was conducted over a period of six months among 43 children of age group 1 month to 14 years of age admitted to the Pediatric Intensive Care unit with a diagnosis of sepsis. Convenience sampling technique was used. The patients were enrolled at admission and daily follow up was done till discharge. Clinical details and outcome were recorded and analyzed through Statistical Package for Social Science version 20.Results:  Out of 43 patients enrolled, 58% were males. The median age of the patients was 3 years (Inter Quartile Range 1, 10).  Respiratory distress was the most common presenting clinical feature. Severe pneumonia (37%) was the most common cause. In this study, 22 (51.2%) patients died. Factors like presence of prior comorbidity, septic shock, Acute Respiratory distress syndrome, Multiple Organ Dysfunction Syndrome, severe sepsis, abnormal finding on chest X ray, hyperlactatemia, metabolic acidosis, ionotropes and Mechanical ventilation use were higher in the Non-survivor group as compared to the survivor group.Conclusion:  This study showed increased mortality in patients having prior comorbidity, septic shock, Acute Respiratory distress syndrome, Multiple Organ Dysfunction Syndrome, severe sepsis, an abnormal finding on chest X ray, hyperlactatemia, metabolic acidosis, use of ionotropes and use of Mechanical ventilation.